Kiai Leadership and Islamic Boarding School Cultural Strategies in Strengthening Religious Moderation in Indonesia - Siti Aimah; Hasan Baharun; Fathiyah Mohd Fakruddin; Eko Budiywono (Edukasia Islamika : Jurnal Pendidikan Islam, 2026)
The present study aims to showcase in depth the unique role of Kiai (Islamic scholars) leadership in institutionalizing and disseminating the narrative of religious moderation in pesantren (Islamic boarding schools), and to explore the cultural strategies these schools use as effective bulwarks in deradicalization efforts. This study was designed with a qualitative, interpretive case study of several traditional and modern pesantren that played a central role in promoting tolerance in Banyuwangi, Indonesia. Data were gathered through in-depth interviews with Kiai and senior santri (pesantren students), participant observation of teaching and learning activities, and documentation of Islamic boarding school records. Study findings demonstrate that the Kiai leadership in Blokagung was uniquely charismatic and collegial, successfully institutionalizing religious moderation through the integration of the Salaf and the modern era and the establishment of UIMSYA. His primary cultural strategy was to instill the values ​​of Aswaja (tawazun, tasammuh) as an ideological inoculation. The Kiai/Nyai became actors who built social resilience grounded in concern and guided the politics of akhlaqi. This made the Islamic boarding school an effective bastion of deradicalization, disseminating moderate narratives in a structured and legitimate manner. The study provides a theoretical framework that contextualizes traditional Kiai leadership as a model of indigenous leadership in counter-extremism, offering valuable insights for global public policy on the use of community-based educational institutions to foster social cohesion and counter-radicalism.